STUDI KETERAMPILAN TEKNIK DASAR SEPAKBOLA SISWA SMP NEGERI 3 KOTA PADANG - ., Erianti; Astuti, Yuni; ., Zulbahri; ., Damrah; ., Kibadra (Universitas Pendidikan Ganesha, 2020)
The problem in this study is that the basic technical skills of student football are not yet known at SMP Negeri 3 Kota Padang. So the purpose of this study was to determine the basic technical skills of student football at SMP Negeri 3 Padang, which consisted of passing, dribbling, shooting and heading techniques. This type of research is descriptive. The population in this study were all students of SMP Negeri 3 Kota Padang who actively participated in soccer training in football extracurricular activities, totaling 22 people. The sampling technique uses total sampling. Thus the sample in this study amounted to 22 people. To obtain data, measurements are made on the basic technical abilities of football. Data were analyzed using percentages. The results found that: the basic technical skills of football students of SMP Negeri 3 Kota Padang, it can be said that there are still many who have not been good, because of 22 students only 1 person (4.54%) category is very good, 7 people (31.82%) good category, and 2 people (9.09%) medium category. The rest students have less basic technical skills in soccer categories, namely 12 people (54.54%).Keywords: Basic Football Techniques.